Indicadores de qualidade do solo em relação à erosão hídrica em sistemas agrícolas utilizando a lógica Fuzzy - Santos, Wharley Pereira dos (2016)
Quantification of soil quality in different agricultural systems is essential to ascertain its current condition. For this, the use of different indicators of quality of the soil through sets of physical and chemical properties is required. Objective with this study the determination of different models of indexation of soil quality for different cover crops grown in many managements systems in the control of soil and water losses by water erosion. The experiment was conducted in annual cycles of cultivation between 2007 and 2014 on the campus of the Federal University of Lavras, Lavras - MG. The soil was classified as Red-Yellow Latosol, from which we evaluated the different species of cover crops, distributed in different cropping systems and in consortium with corn. It was evaluated two models index of soil quality, namely: integrated additive Quality Score and Quality Score Nemoro. Both models showed excellent correlation, but the dating obtained low values in relation to the integrated additive model. Physical and chemical attributes were selected for the composition of a smaller set of soil quality indicators.